2018
DOI: 10.1088/2399-6528/aab007
|View full text |Cite
|
Sign up to set email alerts
|

Widely tunable (2.6–10.4μm) BaGa4Se7optical parametric oscillator pumped by a Q-switched Nd:YLiF4laser

Abstract: We report on the first BaGa 4 Se 7 nanosecond optical parametric oscillator pumped by Q-switched Nd:YLiF 4 laser at 1053 nm. The oscillator exhibits a pump threshold energy as low as 0.25 mJ. Midinfrared (MIR) idler wave tuning from 2.6 μm to 10.4 μm is demonstrated with an angle-tuned type-I (o-ee) y-cut sample, highlighting the superior performance of this novel large bandgap chalcogenide nonlinear crystal to generate tunable coherent radiation over its full MIR transparency range (0.47-18 μm). The phase-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 32 publications
0
10
0
2
Order By: Relevance
“…In 2016, Kostyukova et al [8] used a 1064 nm Nd:Y 3 Al 5 O 12 (Nd:YAG) laser to pump the BGSe OPO, and an ultra-broad tunable range of 2.7-17 μm was obtained, with a maximum pulse energy of 3.7 mJ at 7.2 μm. In 2018, Kolker et al [9] reported on the first, to the best of our knowledge, BGSe nanosecond OPO pumped by a Q-switched Nd:YLiF 4 laser at 1053 nm, and an ultra-broad tunable range of 2.6-10.4 μm was obtained. In 2018, Zhao et al [10] demonstrated a tunable 8-9 μm OPO with a type II phase-matching BGSe pumped by a 2090.7 nm acousto-optical Q-switched Ho:YAG laser, and a spectral bandwidth of 67.8 nm at 8925.7 nm was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Kostyukova et al [8] used a 1064 nm Nd:Y 3 Al 5 O 12 (Nd:YAG) laser to pump the BGSe OPO, and an ultra-broad tunable range of 2.7-17 μm was obtained, with a maximum pulse energy of 3.7 mJ at 7.2 μm. In 2018, Kolker et al [9] reported on the first, to the best of our knowledge, BGSe nanosecond OPO pumped by a Q-switched Nd:YLiF 4 laser at 1053 nm, and an ultra-broad tunable range of 2.6-10.4 μm was obtained. In 2018, Zhao et al [10] demonstrated a tunable 8-9 μm OPO with a type II phase-matching BGSe pumped by a 2090.7 nm acousto-optical Q-switched Ho:YAG laser, and a spectral bandwidth of 67.8 nm at 8925.7 nm was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Several works on 6.45 µm ns MIR generation, from a 1 µm laser based on BGSe-OPO, were reported [19,20]. For example, a ns BGSe-OPO pumped by Q-switched Nd:YLiF 4 laser at 1053 nm was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the newly developed BGSe crystal with high performances is considered as a very promising NLO crystal for widely tunable and high-energy mid-infrared wave generation, especially pumped at 1 μm [12]- [16]. BGSe crystals with long length (14.5-30 mm) have been employed in the widely tunable and high-energy mid-infrared OPO sources, which were pumped by different fixed wavelengths of 1.053 μm, 1.064 μm, 2.1 μm and 2.79 μm under type I and type II phase-matching (PM) conditions [17]- [22] with angle-tuning method. Except for the angle-tuning method, many tuning methods have been employed in the OPO sources instead of tilting the angle of crystals, including temperature-tuning and pump-tuning methods.…”
Section: Introductionmentioning
confidence: 99%